2017
DOI: 10.1111/acps.12844
|View full text |Cite
|
Sign up to set email alerts
|

Are early‐life antecedents of suicide mortality associated with psychiatric disorders and suicidal ideation in midlife?

Abstract: Associations for younger maternal age, higher birth order and adversities with adult internalizing disorders suggest that psychiatric disorders may be on the pathway linking some early-life factors and suicide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…The pattern of association was similar for psychiatric disorders, although the statistical evidence of a dose–response effect was weaker. Few previous studies have investigated the association of birth order and offspring psychiatric disorder, the current study adds support to previous studies that have and that reported later-born children to be at greatest risk of mental health problems, and increased risk of suicide [3, 15, 31]. Any differences in strength of association for outcomes of suicide attempts and psychiatric disorder could reflect a different aetiology of suicidal behaviour [20] and mental health, and the relative contribution of birth order to these outcomes.…”
Section: Discussionsupporting
confidence: 81%
“…The pattern of association was similar for psychiatric disorders, although the statistical evidence of a dose–response effect was weaker. Few previous studies have investigated the association of birth order and offspring psychiatric disorder, the current study adds support to previous studies that have and that reported later-born children to be at greatest risk of mental health problems, and increased risk of suicide [3, 15, 31]. Any differences in strength of association for outcomes of suicide attempts and psychiatric disorder could reflect a different aetiology of suicidal behaviour [20] and mental health, and the relative contribution of birth order to these outcomes.…”
Section: Discussionsupporting
confidence: 81%
“…Age of parents. There were nine studies exploring the association between having teen parents (<20 years old) and depression in offspring in the meta-analysis (Buizer-Voskamp et al, 2011;Geoffroy et al, 2018;Herva et al, 2008;Levine, 2014;Pereira et al, 2012;Slykerman et al, 2015 Figure 2 Pooled ORs for the association between prenatal, perinatal, and postnatal factors and depression risk. Gale 1 is the study among females, Gale 2 is the study among males; Nomura 1 is the New York State Psychiatric Institute/Columbia University study, Nomura 2 is the National Collaborative Perinatal Project (NCPP) study; Pereira 1 study compares depression in children 7-9 years with maternal factors, Pereira 2 study compares depression in children 10-11 years with maternal factors, Pereira 3 study compares depression in children 7-9 years with paternal factors, Pereira 4 study compares depression in children 10-11 years with paternal factors; Joinson 1 study compares depression in children less than 12 years old, Joinson 2 study compares depression in children at 12-16 years old, Joinson 3 study compares depression in children at 12-17 years old; Phillips 1 is the study on prenatal stress, Phillips 2 is the study on prenatal stress; Taylor 1 is the ALSPAC study, Taylor 2 is the HUNT study, and Taylor evidence of heterogeneity between studies (I = 32%, p = .16).…”
Section: Biological Factorsmentioning
confidence: 99%
“…On the basis of this study and the comparison of three trajectories of peer-victimization-low, moderate, and severe from the ages of 6-13 years old-MGSS researchers report that adolescents who were more severely victimized throughout their school journey are "at greater chance of suicidality in adolescence than less severely victimized children, even accounting for a plethora of confounders assessed throughout childhood" (Geoffroy et al, 2018a, p. 41). Another cohort study of interest to the team is the 1958 National Child Development Study (NCDS) based in Britain, in which these researchers further identified perinatal risk factors (e.g., young maternal age), and developmental risk factors (i.e., externalizing behaviors) and correlated these with the number of childhood adversities that were associated with suicidality later in life (Geoffroy et al, 2018b). The findings produced through these cohort study analyses, thus far, are consistent with those from previous ACEs studies (Anda et al, 2006), in which researchers identified "a dose-response association between the number of emotional adversities and suicide, with the highest suicide risks [found] among those experiencing three or more adverse experiences" (Geoffroy et al, 2014, p. 10).…”
Section: Modeling Early Adversity As a Major Risk Factormentioning
confidence: 99%